Provision of green areas in functional zones of Voronezh city - Kristina A. Plotnikova; Sergey N. Kirillov (RUDN Journal of Ecology and Life Safety, 2025)
The relevance of this study is tied to the growing need for effective management of urban green spaces, which play a key role in maintaining ecological balance and enhancing the quality of life for city residents. In the context of intense urbanization, cities face challenges related to the disruption of ecosystem functions within green areas. The main aim of this paper is to conduct a geoecological assessment of the state of urban greenery in the city of Voronezh using modern methods, including the calculation of significance coefficients for dendrological indicators. The comprehensive approach applied in this article combines traditional ecological diagnostic methods with consideration of dynamic environmental changes. The results indicate a significant contrast in the spatial distribution of green areas in Voronezh, which is linked to urban planning characteristics and anthropogenic impacts. The most extensively greened areas are the natural-recreational and special zones, whereas residential and industrial areas require improvements in their greening. The conclusion emphasizes that to improve the state of urban green spaces in Voronezh, further research should consider changes in ecological factors, alongside refining geoecological assessment methods to foster the development of more resilient urban ecosystems.